Bioeconomic Analysis of Dorab Wolf-Herring (Chirocentrus dorab) in the Waters of North Rupat District, Bengkalis, Riau - Vazira, Era; Zulkarnaini, Zulkarnaini; Arief, Hazmi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2026)
North Rupat District is one of the areas located in Bengkalis Regency and is on the border of the Republic of Indonesia with the Malacca Strait. This district has considerable fisheries potential in producing catches, especially dorab wolf-herring (Chirocentrus dorab). This study aims to analyze the level of effort and catch of dorab wolf-herring under MSY (Maximum Sustainable Yield), MEY (Maximum Economic Yield), and OA (Open Access), calculate economic rents, and analyze the level of utilization of dorab wolf-herring resources in the waters of North Rupat District. This research was conducted using a survey method through direct field interviews using a questionnaire. The data analysis used was bioeconomic analysis using the five-model approach estimation. The results showed that dorab wolf-herring production in the waters of North Rupat District, under optimal conditions, was at the MEY condition, namely at a production level of 313.34 tons/year with an effort level of 415 units/year. The optimum profit obtained at the highest utilization of dorab wolf-herring resources is at the MEY condition, which is IDR 7,846,772,695, and the level of dorab wolf-herring resource utilization is obtained at 55%, which means that it has not experienced overfishing both economically and biologically.